Risk‐adjusted analysis of perioperative outcomes after the Sistrunk procedure - Erin M. Wynings; Cynthia S. Wang; Shyon Parsa; Romaine F. Johnson; Christopher C. Liu (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objectives Thyroglossal duct cyst (TGDC) is the most common pediatric congenital neck mass. The Sistrunk procedure is the standard method of excision and is associated with low rates of recurrence. This study aimed to review our institution's outcomes following the Sistrunk procedure, specifically the rates of wound complications and cyst recurrence. Methods This was a retrospective case series of pediatric patients undergoing the Sistrunk procedure from June 2009 to April 2021. Results A total of 273 patients were included. Of these, 139 (53%) patients were male and 181 (66%) were white. The average age at the time of surgery was 7.1 years. The overall cyst recurrence rate was 11%. The most common wound complications were seroma (14%) and surgical site infections (SSIs) (12%). Wound complications were associated with prior history of cyst infection (odds ratio [OR] 1.97, 95% confidence interval [CI] 1.07–3.60, z‐test 2.2, p = .03). Pediatric surgery was associated with fewer wound complications (OR 0.18; 95% CI 0.05–0.6, z‐test −2.78, p = .005). However, pediatric surgery operated on fewer patients with a history of cyst infection (36% vs. 55%, p = .012). Drain placement and postoperative antibiotics did not affect rates of wound complications. Conclusions Prior cyst infection is associated with increased rates of postoperative wound complications. Postoperative antibiotics and drain placement did not significantly affect complication rates. Level of Evidence 4.